Microstructure, hot oxidation resistance and damping capacity of Al- alloyed cast iron. (4th March 2017) - Ibrahim, Mervat Mohamed; Mourad, Mohamed Mahmoud; Nofal, Adel Abdelmonem; Farahat, Ahmed I. Z.
Abstract: Ductile cast iron was developed by adding Aluminium (up to16 wt%Al). Effects of aluminium on microstructure, hardness, oxidation resistance at high temperature and damping capacity of cast iron were studied. Adding Al up to 4.0 wt% raised degree of graphitisation. More than 4.0 wt% up to 13.8 wt%Al showed precipitation of hard carbides. Hardness was increased signiﬁcantly by increasing Al due to formation of intermetallic compounds. More than 5.8 wt%Al showed a higher oxidation resistance due to formation of complex Fe-Al oxide, acted as a protective and adherent scale. Damping capacity of 2.6 and 4.0 wt%Al was increased as the volume fraction of graphite increased as well as the change of graphite from spheroidal to compacted ones. Damping capacity of 16 wt%Al was enhanced due to high ferrite (86%) containing graphite. However, decreasing of ferrite and disappearing of graphite as well as presence of carbides highly deteriorated damping capacity of 5.8, 9, 12.8 and 13.8 wt%Al cast iron.